Innovation and investment activities of construction enterprises: advantages and disadvantages of development in Ukraine under war conditions - Tsimoshynska, Oksana; Ivanova, Tatiana (Ways to Improve Construction Efficiency, 2024)
The article examines the peculiarities of the innovation and investment activities of construction enterprises in Ukraine under the conditions of military conflict, which create unprecedented challenges and new opportunities for the industry. The advantages of implementing modern technologies such as digital platforms, BIM modeling, artificial intelligence, and process automation are explored, which contribute to improving efficiency, optimizing costs, ensuring transparency, and speeding up the implementation of construction projects. Special attention is paid to the use of artificial intelligence technologies for automating routine operations, allowing construction companies to reduce risks, improve construction quality, and enhance safety on construction sites. An overview of the main problems in the industry is provided, including financial instability, which limits access to capital for implementing capital-intensive projects, disruptions in material supply chains due to logistical breakdowns, a shortage of qualified personnel resulting from migration processes and the economic crisis, as well as increased risks for investors due to market uncertainty. The authors examine the key elements of the strategic plan for developing the innovation and investment potential of the construction business, which form the basis for the sustainable and effective development of the industry. First, emphasis is placed on the importance of business strategy, which defines the main priorities and mechanisms for achieving the company’s goals, as well as the relationship between business and innovation strategies. The innovation development goals, including the implementation of new technologies and improving energy efficiency, are discussed. The second component, the introduction of market data, includes elements such as customer needs, regulation, technologies, and competitive environment analysis, which contribute to forming effective management decisions. The role of each of these components in creating innovative solutions to meet market demands, considering current legislation, and using modern technologies to improve the quality and efficiency of construction processes is highlighted. The need to create favorable conditions for the development of enterprises in the post-war period is identified, particularly through the improvement of the regulatory and legal framework, providing state support, stimulating innovation activities, and integrating the construction sector of Ukraine into European markets.